(Re)theorising laddish masculinities in higher education. Issue 7 (10th November 2017) - Phipps, Alison
ABSTRACT: In the context of renewed debates and interest in this area, this paper reframes the theoretical agenda around laddish masculinities in UK higher education, and similar masculinities overseas. These can be contextualised within consumerist neoliberal rationalities, the neoconservative backlash against feminism and other social justice movements, and the postfeminist belief that women are winning the 'battle of the sexes'. Contemporary discussions of 'lad culture' have rightly centred sexism and men's violence against women: however, we need a more intersectional analysis. In the UK a key intersecting category is social class, and there is evidence that while working-class articulations of laddism proceed from being dominated within alienating education systems, middle-class and elite versions are a reaction to feeling dominated due to a loss of gender, class and race privilege. These are important differences, and we need to know more about the conditions which shape and produce particular performances of laddism, in interaction with masculinities articulated by other social groups. It is perhaps unhelpful, therefore, to collapse these social positions and identities under the banner of 'lad culture', as has been done in the past.